PEMIDANAAN TERHADAP TINDAK PIDANA MENDISTRIBUSIKAN FOTO PORNOGRAFI MENGGUNAKAN AKUN FACEBOOK - Rayhan Sheperd Dwicahyo Pramudito; Azmi Syahputra (Reformasi Hukum Trisakti, 2022)
A single indictment namely, Article 45 Paragraph 1 in conjunction with Article 27 Paragraph 1 of Law Number 19 of 2016 concerning Information and Electronic Transactions as in Decision Number 12 /Pid.Sus/2020/PN Mjn is used to punish those who spread pornographic images using a Facebook account. There are two articles that are identical to each other in Indonesia. How to apply the elements to those committing the crime of distributing or disseminating pornographic images using a Facebook account is the formulation of the issue, as is whether the decision on the criminal act of distributing or disseminating pornographic images using a Facebook account in Decision Number 12/Tip.Sus/2020/PN Mjn in keeping with the intended outcome of the sentence? By combining analytical descriptive research with normative research, the following can be accomplished. Article 45 Paragraph 1 serves as the legal foundation for the conviction for the crime of disseminating pornographic images using a Facebook account. Jo Article 27, Section 1 In terms of the Criminal Code and electronic information, UU ITE is lex specialis and lex consumer, respectively The Pornography Law. The judge in this situation should decide to distribute or make accessible rather than transmit the information.